2005
DOI: 10.1002/pmic.200401149
|View full text |Cite
|
Sign up to set email alerts
|

Towards royal jelly proteome

Abstract: The recent availability of the honey-bee Apis mellifera genome and trascriptome of both the female castes, has stimulated new efforts in investigating the protein composition of royal jelly (RJ), its role in caste differentiation and its quality and typicality by a proteomic approach. This study is aimed both to separate and identify proteins of royal jelly and to detect some of them in honey-bee pollen-bread by using two-dimensional gel electrophoresis, mass spectrometry and by de novo sequencing. All the ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
1
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 39 publications
5
83
1
4
Order By: Relevance
“…We assume that recombinant protein fragments do not contain specific sequences, which are necessary for proteolytic degradation by a complex of proteases from E. coli, particularly trypsin-like proteases. Moreover, the degradation of native monomeric, but not oligomeric, form of Apa1 in RJ was also observed [19,[42][43][44]. It has been recently indicated that Apa1 in RJ is specifically degraded by unknown metalloproteinase(s), which seem to have restricted substrate specificity [43].…”
Section: Discussionmentioning
confidence: 95%
“…We assume that recombinant protein fragments do not contain specific sequences, which are necessary for proteolytic degradation by a complex of proteases from E. coli, particularly trypsin-like proteases. Moreover, the degradation of native monomeric, but not oligomeric, form of Apa1 in RJ was also observed [19,[42][43][44]. It has been recently indicated that Apa1 in RJ is specifically degraded by unknown metalloproteinase(s), which seem to have restricted substrate specificity [43].…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have analysed MRJPs by reducing SDS-PAGE, including 2-DE Sano et al, 2004;Santos et al, 2005;Scarselli et al, 2005;Schmitzova et al, 1998;Schonleben et al, 2007). Separated bands on SDS-PAGE do not reflect the data for intact proteins, as samples are boiled and reduced as part of the standard Laemmli (1970) method.…”
Section: Proteins Peptides and Amino Acidsmentioning
confidence: 99%
“…Perchloric acid is the commonly used agent to extract ATP-related compounds from intact cells due to its strong acidic nature, and it can precipitate protein effectively (Coolen et al, 2008;Fukuuchi et al, 2013). RJ is a complex matrix containing several proteins (Scarselli et al, 2005) which needs to be removed before analysis. Use of higher concentration of ethanol, acetone or perchloric acid helps to precipitate the protein effectively from the RJ samples (Zhou et al, 2007).…”
Section: Optimisation Of Extraction Methodsmentioning
confidence: 99%